2011
DOI: 10.2741/3797
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral thermoregulation in mammals: a review

Abstract: In mammals, thermoregulation is a key feature in the maintenance of homeostasis. Thermoregulatory capacities are strongly related to energy balance and animals are constantly seeking to limit the energy costs of normothermia. In case of thermal changes, physiological mechanisms are enhanced, increasing rates of energy expenditure. However, behavioral adjustments are available for species to lower the autonomic work, and thus reduce the energy costs of thermoregulatory responses. Hence, thermogenesis-induced me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
270
1
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(281 citation statements)
references
References 179 publications
2
270
1
8
Order By: Relevance
“…In the study area, days with higher minimum temperatures generally experienced higher maximum temperature, which might have placed the possums under heat stress. Several mammalian species have been observed to decrease their food intake and activity under heat stress in order to reduce their heat production (Terrien et al 2011). P. occidentalis may employ similar behavioural coping mechanisms and thus reduce their activity, including bridge crossings, on warmer nights.…”
Section: Discussionmentioning
confidence: 99%
“…In the study area, days with higher minimum temperatures generally experienced higher maximum temperature, which might have placed the possums under heat stress. Several mammalian species have been observed to decrease their food intake and activity under heat stress in order to reduce their heat production (Terrien et al 2011). P. occidentalis may employ similar behavioural coping mechanisms and thus reduce their activity, including bridge crossings, on warmer nights.…”
Section: Discussionmentioning
confidence: 99%
“…Keeping all this in mind, the most efficient way to conserve energy is by seeking an optimal environment in terms of energy savings before changes in temperature occur, in which the organism can attain "thermoneutrality, " which all depends on an idiosyncratic level of comfort for the animal. In other words, the level of comfort relies on metabolic activity (Terrien et al, 2011), which differs across organisms, across the lifespan, and across social contexts.…”
Section: Social Thermoregulation Saves Energy: Thermoregulation Acrosmentioning
confidence: 99%
“…Supporting this idea, vagal tone is associated with social wellbeing and social support seeking (Geisler et al, 2013). for infants. Further, many animals also do so reciprocally, as adult birds and mammals shield each other from harsh climatic environments through huddling (Gilbert et al, 2007;Terrien et al, 2011). We now turn to examples from the animal literature where huddling as a means for social thermoregulation has been detected.…”
mentioning
confidence: 99%
“…7 C and D) suggesting that tumor growth eventually exhausted the ability of mice to maintain normal body temperature under subthermoneutral conditions. It is well known that when mice are required to increase their metabolic heat production via thermogenesis, they exhibit long-conserved behavioral changes associated with "feeling cold," provoking them to move to warmer ambient temperatures, thus minimizing thermogenesis (3,4,8,22). Because caged mice are unable to carry out this behavioral activity, a thermal preference determination is frequently used to measure the degree of cold stress/heatseeking activity in laboratory mice (6).…”
Section: Cd8mentioning
confidence: 99%
“…This factor is important because mice have a high surface area to body mass ratio and lose heat rapidly. In nature, mice seek warm environments and build nests to minimize metabolic demands for heat production (3), and thermal preference studies have clearly shown that healthy mice will select an ambient temperature of 30-31°C (termed "thermoneutrality") at which their basal metabolism is sufficient to maintain body temperature (3)(4)(5)(6)(7). However, at subthermoneutral temperatures, mice experience cold stress, which induces a systemic sympathetic response involving adaptive metabolic changes and secretion of catecholamines, particularly norepinephrine (8).…”
mentioning
confidence: 99%